2015
DOI: 10.1177/0539018415597316
|View full text |Cite
|
Sign up to set email alerts
|

The two sides of disgust: A lexical and thematic content analysis of narratives of personally experienced physical and moral disgust

Abstract: The present study examined narratives about situations in which individuals experience physical and/or moral disgust, and the similarities and differences between them. A thematic content analysis of participants' narratives of personal physically or morally disgusting experiences as well as a lexical analysis using the computer program ALCESTE revealed that physical disgust emerges in an instantaneous reflex-like way during situations in which the individual is directly exposed to physical disgust elicitors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Core disgust and moral disgust are also different in their relationships to other emotional responses. Specifically, moral disgust stimuli, but not core disgust stimuli, also tend to elicit anger and sadness (Abitan & Krauth-Gruber, 2015; Marzillier & Davey, 2004; Simpson et al, 2006), whereas core disgust has been found to correlate with fear (Olatunji, Tolin, Huppert, & Lohr, 2005).…”
Section: Core Disgust and Moral Disgustmentioning
confidence: 98%
See 4 more Smart Citations
“…Core disgust and moral disgust are also different in their relationships to other emotional responses. Specifically, moral disgust stimuli, but not core disgust stimuli, also tend to elicit anger and sadness (Abitan & Krauth-Gruber, 2015; Marzillier & Davey, 2004; Simpson et al, 2006), whereas core disgust has been found to correlate with fear (Olatunji, Tolin, Huppert, & Lohr, 2005).…”
Section: Core Disgust and Moral Disgustmentioning
confidence: 98%
“…The distinction between core disgust and moral disgust has led to an ongoing debate about whether the two types of disgust represent two distinct emotions (Abitan & Krauth-Gruber, 2015; S. Lee & Ellsworth, 2013;Luo et al, 2013;Marzillier & Davey, 2004;Moll et al, 2005;Nabi, 2002;Simpson, Carter, Anthony, & Overton, 2006;Yang, Li, Xiao, Zhang, & Tian, 2014;Yoder, Widen, & Russell, 2016) or two manifestations of a single emotion (Chapman & Anderson, 2013;Chapman, Kim, Susskind, & Anderson, 2009;Danovitch & Bloom, 2009;Jones & Fitness, 2008;Rozin et al, 2008). Two central features that core disgust and moral disgust share are their similar facial motor activity and similar behavior response.…”
Section: Core Disgust and Moral Disgustmentioning
confidence: 99%
See 3 more Smart Citations